Methane production potential of feed ingredients estimated by in vitro gas production test - M.Ramachandran; A. Bharathidhasan; V.Balakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was conducted to investigate methane production potential of feed ingredients to develop a database on methane production. Feed ingredients such as cereal grains, cereal by-products and protein supplements were tested for methane production potential using in vitro gas production technique. In vitro true digestibility (IVTD) of cereal grains ranged from 60.1 to 96.7% and oats grain (76.2%) and distiller’s grain (60.1%) had lower (P